Updates on antifungal pharmacotherapy in elasmobranchs: pharmacokinetics of 4 mg/kg voriconazole after IM and IV administration in undulate skates (Raja undulata) maintained under human care - Cañizares-Cooz, Daniela; Rojo-Solís, Carlos; Rubio-Langre, Sonia; García-Párraga, Daniel; Encinas, Teresa; Morón-Elorza, Pablo (Frontiers in Veterinary Science, 2024)
Fungal diseases are frequently associated with elevated mortality rates in elasmobranchs. Currently, there is a notable absence of scientifically validated therapeutic medications that can ensure both effectiveness and safety when administered to this group of animals. The empirical prescription of azole antifungal agents, particularly voriconazole, has been posited as a potentially efficacious treatment approach for addressing most common mycoses in sharks and rays. However, there are still no published pharmacokinetic studies supporting its use in elasmobranchs and there is a lack of scientific base for its utilization in elasmobranchs. For this study, voriconazole was administered intravenously (IV) and intramuscularly (IM), at a single dose of 4 mg/kg to six adult undulate skates (Raja undulata). A washout period of eight weeks was left between each route of administration. Blood samples were collected both before and at ten predetermined intervals after each dosing (0.25, 0.5, 1, 1.5, 2, 4, 8, 12, 24, and 36 hours after drug administration). Plasma concentrations were quantified using a validated high-performance liquid chromatography method, and pharmacokinetic (PK) data was analyzed through non-compartmental methods. The mean extrapolated concentration at 0 h (C0) after IV administration was 27.19 ± 7.15 µg/ml and the mean peak plasma concentrations (Cmax) ± SEM after IM administration resulted 2.98 ± 0.28 µg/ml at a mean time to maximum concentration (T max) of 1.33 ± 0.17 hours. Terminal half-lives were calculated and resulted 11.18 ± 1.32 hours for IV injections and 9.59 ± 1.38 hours for IM injections. The area under the curve extrapolated to infinity was determined as 58.14 ± 2.79 hours·µg/ml following IV injections and 37.60 ± 6.67 hours·µg/ml following IM injections. The IM-administered voriconazole exhibited a mean absolute bioavailability of 64.67 ± 11.47%. These discoveries provide backing for the possible application of voriconazole through the intramuscular route in undulate skates and support using lower dosage regimens compared to those required for oral administration, emphasizing the importance of conducting further pharmacokinetic studies with antifungals in elasmobranchs.